1998
DOI: 10.1021/bi981883y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Truncated and Glycosylation-Deficient Forms of the Cation-Dependent Mannose 6-Phosphate Receptor Expressed in Baculovirus-Infected Insect Cells

Abstract: A soluble truncated form of the cation-dependent mannose 6-phosphate receptor (CD-MPR) encoding only the extracytoplasmic region, Stop155, and a truncated glycosylation-deficient form of the CD-MPR, Asn81/Stop155, which has been modified to contain only one N-linked glycosylation site at position 81 instead of five, were purified from baculovirus-infected High Five insect cells. The glycosylated recombinant proteins were functional in ligand binding and acid-dependent dissociation as assessed by pentamannosyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…contain M6P, as a component of the cell wall, teichoic acids, lipoteichoic acids, or other virulence factors, that is available to interact with IGFIIR during pathogenesis. The carbohydrate binding site of the IGFIIR in domain 3 has been shown to recognize related structures such as phosphodiesters or mannose 6-sulfate (54,55,81), and the interaction of Listeria spp. with the IGFIIR may be based on such a related structure that is present on the cell surface of Listeria bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…contain M6P, as a component of the cell wall, teichoic acids, lipoteichoic acids, or other virulence factors, that is available to interact with IGFIIR during pathogenesis. The carbohydrate binding site of the IGFIIR in domain 3 has been shown to recognize related structures such as phosphodiesters or mannose 6-sulfate (54,55,81), and the interaction of Listeria spp. with the IGFIIR may be based on such a related structure that is present on the cell surface of Listeria bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Sf9 cells were grown in serum-free BD BaculoGold Max-XP medium (Pharmingen) as suspension cultures to a density of 3 ϫ 10 6 cells/ml and were subsequently infected with recombinant baculovirus at a multiplicity of infection of ϳ3. The medium was harvested 5 days after infection, and recombinant protein was purified to near homogeneity by affinity chromatography as described previously (15) except that phosphomannan-Sepharose was used as the affinity resin instead of pentamannosyl-phosphate agarose. Prior to crystallization, proteins were dialyzed extensively at 4°C in the indicated buffer (see supplemental Table 1).…”
Section: Expression Purification and Crystallization Of The Extracymentioning
confidence: 99%
“…We have previously shown that a truncated, glycosylation-deficient form of the bovine CD-MPR (Asn-81/STOP 155 ), which lacks the transmembrane and cytoplasmic regions of the receptor and contains only a single N-glycosylation site, binds the lysosomal enzyme, ␤-glucuronidase, with an affinity identical to that of the full-length wildtype receptor (24). Our recent success in crystallizing Asn-81/ STOP 155 in the presence of Man-6-P (20) or pentamannosyl phosphate (21) has resulted in the three-dimensional structure of the extracytoplasmic region of the CD-MPR and has identified nine residues (Tyr-45, Gln-66, Asp-103, Asn-104, His-105, Arg-111, Glu-133, Arg-135, and Tyr-143) that are involved in binding Man-6-P (Figs.…”
Section: Site-directed Mutagenesis Of Residues In the Binding Pocket mentioning
confidence: 99%